Procedures and criteria to develop and evaluate household sustainable consumption indicators - Caeiro, Sandra (2021)
Communication about very complex problems like household sustainable consumption in simple terms is still a major challenge. Despite the diversity of tools to measure household consumption, clearer indicators are needed to more effectively communicate with the general public. The main objective of this research was to develop an approach to define the main procedures and criteria to built household sustainable consumption assessment tools based on indicator sets. A review of available household sustainable consumption assessment metrics and related initiatives was conducted; this included a comparative analysis of the different approaches. The review revealed that the majority of these initiatives are focused upon specific domains (e.g. energy or waste), but none used an integrated approach in the sustainable consumption domains. Furthermore, it was found that few methods used indicators to measure and assess household sustainable consumption. Principal components and a checklist of key good-practice factors that a household sustainable consumption indicator system should include were developed. Due to the need to communicate effectively, to engage stakeholders and to address the complexity involved in the measurement and assessment of household sustainable consumption, the proposed integrated approach was designed to evaluate household sustainable consumption.